Reflection of nature in the material culture of the Karbi tribe: A case from Kamrup (M) district, Assam, India (Geographical Journal of Nepal, 2022)
The processes of nature-culture interaction and resulting landscapes in an area form fertile fields for geographical research. The present study is an attempt to analyse the reciprocal relation between people and nature in a tribal village environment of the Brahmaputra Valley, Assam. Based on intensive field survey and interviews with the inhabitants, the study reveals that the human-environment relationship in the village is still mutually helpful and more or less sustainable. However, perceptible changes have occurred in the traditional cordial relationship between the people and their environment in respect of habitat, economy and mode of living mainly due to the growing influence of modernization.